Implementasi Pendekatan Joyfull Learning pada Pembelajaran Pendidikan Agama Katolik untuk Meningkatkan Motivasi Belajar Peserta Didik di SDK Carmen Salles Weri (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by the lack of learning motivation of students in Catholic religious education learning at SDK Carmen Salles Weri, which is seen from the less than optimal joyful learning approach, making students at the school less motivated to learn. The purpose of this study was to determine how the implementation of the joyful learning approach in Catholic religious education learning can improve student learning motivation at SDK Carmen Salles Weri. The type of research used is qualitative with a descriptive approach. The results of the study stated that the implementation of the joyful learning approach in PAK learning can improve student learning motivation. The joyful learning approach carried out at SDK Carmen Salles Weri has been carried out well so that it increases student learning motivation.